INTEGRATION OF WIND POWER PLANTS TO THE GRID AND REACTIVE POWER_x000D_ SUPPORT - (:unkn) unknown (My University, 2019)
The conversion of wind energy into electrical energy is one of the mostenvironmentally sustainable methods of energy today. According to statisticspublished by the World Wind Energy Association, the total capacity of windturbines installed worldwide at the beginning of 2019 exceeded 598 GW.Looking at the situation in Turkey, the number of wind power plants underoperation is 180 according to published statistics at January 2019 by theTurkish Wind Energy Association. The total installed capacity of these powerplants is 7369.35 MW. By the increasing of wind power capacity, theconnection criteria of the power plants which are taken over to the gridbecome more critical. Although there are systems that are clean, renewable,and reduce external dependence on energy, power quality problems can occurin the grid connections of all wind power plants. In this respect, the gridconnection criteria of wind turbines of the countries are essential. Theconnection requirements of wind turbines in Turkey, on April 22, 2017,revised Turkish Grid Code are determined under Appendix-18. Wind powerplants connect to the grid from a medium voltage or high voltage level. At thegrid connection point, there are some conditions that the plant must be metlike changing wind conditions, switching, fault, etc. These requirements canbe summarized as reactive power support, frequency response, contributionto the post-fault system. In this study, the reactive power capacity of a 9x3.6MW Wind Power Plant to the grid is simulated and investigated.